Prognostic and predictive factors of eribulin in patients with heavily pre-treated metastatic breast cancer. Issue 47 (24th November 2021) - Chen, Pei-Hsin; Yeh, Dah-Cherng; Tung, Heng-Hsin; Lin, Chin-Yao
Abstract : Abstract: A predictive marker for efficacy of eribulin administered as different lines of treatment in metastatic breast cancer (MBC) has not been identified. We aimed to determine the predictive factors for efficacy of eribulin administered as different lines of treatment in MBC patients. This restrospective cohort study included 49 heavily pre-treated MBC patients who received either eribulin monotherapy or combination therapy with eribulin and anti-Her2 therapy. Associations between clinical response of eribulin-based treatment, time-to-treatment failure (TTF), and possible predictive markers were investigated. Patients' median age was 55 years; 65% were ER+; 43% were HER2+; and 16% were triple-negative. Median TTF was 5.23 months and longer in non-visceral metastases patients. Eastern Cooperative Oncology Group (ECOG) status was 0–1; eribulin as ≥2nd-line treatment; eribulin combined with dual blockades; lymphocyte-monocyte ratio (LMR) ≥3; and monocyte-lymphocyte ratio (MLR) <0.4. In patients with eribulin as >3rd-line treatment, univariate analysis showed that ECOG status was 0–1, and LMR ≥3 and MLR <0.4 were associated with a low risk of TTF. Multivariate analysis showed that ECOG status 0–1 was an independent protective factor. Leukopenia and neutropenia were the most common manageable adverse events. ECOG status is an independent predictor for TTF, while LMR and MLR may have an interactive effect with other biomarkers (e.g., ECOG status) to predict response in MBC patients receiving eribulin as ≥2nd-line treatment. Abstract : Supplemental Digital Content is available in the text